MENGOPTIMALKAN PEMBELAJARAN CLOUD-BASED & BLENDED LEARNING: TINJAUAN LITERATUR TERINTEGRASI - Harahap, Sarwedi; Hendra; Napitupulu, Zulhamdani (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
This study is a literature review aimed at identifying and analyzing the implementation of cloud-based learning and blended learning in the context of modern education. By exploring various sources, ranging from books to scholarly journals, this research examines the benefits, challenges, and opportunities offered by these two learning methods. The review findings indicate that the use of cloud-based learning provides flexibility in accessing and distributing learning materials in real time, while blended learning integrates the advantages of online and face-to-face instruction to enhance student interaction and engagement. This study also reveals that the development of technological infrastructure, professional development for educators, and the design of adaptive curricula are key factors in optimizing both learning methods. The findings are expected to serve as a guide for educational practitioners and policymakers in designing innovative and effective learning systems.